Tumor Killing by CD4+ T Cells Is Mediated via Induction of Inducible Nitric Oxide Synthase-Dependent Macrophage Cytotoxicity - Fauskanger, Marte; Haabeth, Ole Audun Werner; Skjeldal, Frode Miltzow; Bogen, Bjarne; Tveita, Anders Aune (Frontiers in Immunology, 2018)
CD4+ T cells can induce potent anti-tumor immune responses. Due to the lack of MHC class II expression in most cancer cells, antigen recognition occurs indirectly via uptake and presentation on tumor-infiltrating antigen-presenting cells (APCs). Activation of the APCs can induce tumor rejection, but the mechanisms underlying tumor killing by such cells have not been established. To elucidate the molecular basis of CD4+ T-cell mediated tumor rejection, we utilized a murine model of multiple myeloma, in which the T cells recognize a secreted tumor neoantigen. Our findings demonstrate that T cell recognition triggers inducible nitric oxide synthase (iNOS) activity within tumor-infiltrating macrophages. Diffusion of nitric oxide into surrounding tumor cells results in intracellular accumulation of toxic secondary oxidants, notably peroxynitrite. This results in tumor cell apoptosis through activation of the mitochondrial pathway. We find that this mode of cytotoxicity has strict spatial limitations, and is thus restricted to the immediate surroundings of the activated macrophage, thus limiting bystander killing. These findings provide a molecular basis for macrophage-mediated anti-tumor immune responses orchestrated by CD4+ T cells. Since macrophages are abundant in most solid tumors, evoking the secretion of nitric oxide by such cells may represent a potent therapeutic strategy.